(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
Gamification, or the use of game elements in non-game environments, has emerged as a transformative method for English as a Foreign Language (EFL) instruction. This study investigates how digital game-based learning (DGBL) affects learner engagement, motivation, and language competency among secondary-level EFL students in Uzbekistan. The study shows, using a mixed-methods approach that includes classroom observation, pre- and post-tests, and student interviews, that gamified learning environments promote active involvement, reduce language fear, and improve communicative competency. The findings highlight the pedagogical value of integrating gaming dynamics with language learning objectives, as well as practical techniques for EFL teachers looking to establish dynamic, learner-centered classrooms.